2022
DOI: 10.1177/09612033221088209
|View full text |Cite
|
Sign up to set email alerts
|

Health care utilization and costs of systemic lupus erythematosus in the United States: A systematic review

Abstract: Objectives To evaluate health care utilization and costs for patients with systemic lupus erythematosus (SLE) by disease severity. Methods We searched PubMed and Embase from January 2000 to June 2020 for observational studies examining health care utilization and costs associated with SLE among adults in the United States. Two independent reviewers reviewed the selected full-text articles to determine the final set of included studies. Costs were converted to 2020 US $. Results We screened 9224 articles, of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Other items reported in this systematic review (like individual drug consumes) could not be compared with our results since we have not individualized each drug separately. 30 Many studies have evaluated costs in the caring of patients with SLE through quantification of HCRU. The relationship between severity of lupus and disease costs has been demonstrated in cohorts from different countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other items reported in this systematic review (like individual drug consumes) could not be compared with our results since we have not individualized each drug separately. 30 Many studies have evaluated costs in the caring of patients with SLE through quantification of HCRU. The relationship between severity of lupus and disease costs has been demonstrated in cohorts from different countries.…”
Section: Discussionmentioning
confidence: 99%
“…Other items reported in this systematic review (like individual drug consumes) could not be compared with our results since we have not individualized each drug separately. 30…”
Section: Discussionmentioning
confidence: 99%
“…SLE is associated with a high economic burden on the healthcare system, with mean annual all-cause healthcare costs per patient in the USA between US$17,258 and US$63,022 [11][12][13][14]. Although data are somewhat limited, several studies have shown that patients with LN incurred between two and four times the healthcare resource utilization (HCRU) and costs compared with patients with SLE without LN and between two and six times the costs of matched controls without SLE [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of autoimmune disease is estimated to be between 3-5% worldwide ( 7 ), and it is a well-established fact that rates of diagnosis are on the rise. The reported mean annual direct costs per patient with systemic lupus erythematosus (SLE) are somewhere between $17,258 and $63,022 regardless of the presence of nephritis ( 8 ). Considering all patients with SLE, this equates to $1.4 to $3.2 billion per year ( 9 ), and this is but one of over a 100 distinct disease entities.…”
Section: Introductionmentioning
confidence: 99%